"A Royal Geographical Society for Ladies": The Lyceum Club and Women's Geographical Frontiers in Edwardian London. Issue 4 (2nd October 2017) - Keighren, Innes M.
Abstract : This article reconstructs the history, organization, and campaigning function of the Geographical Circle of the Lyceum Club—a membership group that, under the leadership of Bessie Pullen-Burry (1858–1937), sought to promote and legitimize women's geographical work in early twentieth-century Britain. Through an examination of archival material and contemporary press coverage, I document the Geographical Circle's efforts to establish itself as a professional body for women geographers and to lobby for their admission to the Royal Geographical Society. Although considerable scholarly attention has been paid to women geographers' individual contributions to the discipline, their cooperative, professionalizing endeavors have been comparatively neglected. In tracing the parallel history of the Circle as an example of women's self-organization, and of Pullen-Burry as an independent campaigner, I argue that a nuanced account of women's professionalization in geography demands attention to both individual and collective endeavors.